EXPLORATORY ARCHAEOLOGICAL EXCAVATIONS IN OLD MARAY. A COLONIAL SETTLEMENT IN THE REGION CHECRAS - Noriega Gutiérrez, Aldo (2015)
This research shows evidence from the archaeological focus on the chronology found in the basement of the colonial site called Maray Viejo. The chronological data represented by the ethnohistorical and archaeological data, provides evidence that the site was occupied by the Spaniards in the sixteenth century. Evidence of the existence of materials and structures in the basement of colonial settlement, by principles of partnership and overlap would be prehispanic are also presented.